INVESTIGATION INTO OPEN EDUCATIONAL RESOURCES FOR LEARNING ENGLISH IN DEVELOPING FUTURE PHILOLOGISTS’ INSTRUMENTAL VALUES - Malykhin, Oleksandr; Aristova, Nataliia; Kovalchuk, Vasyl (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The authors present the results of the research carried out in the 2016/2018 academic years among 338 students earning BA in the English language and literature regarded in our study as future philologists. Experimental work was conducted at four higher educational institutions in Ukraine. The aim of the study was to find out the influence of open educational resources for learning English on the development of future philologists’ instrumental values. We used methods of mathematical statistics, computer data processing and a descriptive method for interpreting experimental data. The authors theoretically substantiate and practically prove the efficiency of the use of open educational resources for learning English which influence the development of future philologists’ instrumental values necessary for adequate evaluating own activity and meeting various real-life and professional challenges. These open educational resources are The Internet Encyclopedia of Ukraine, Encyclopedia Britannica, The Cambridge History of English and American Literature, Learn English. The results obtained in the experimental and control groups are compared and conclusions on the efficiency of the use of open educational resources for learning English in the educational process of higher education institutions in the context of development of future philologists’ instrumental values are drawn.